Seasonal Variation of Growth Characteristics in some Selected Tree Saplings - Naidu, C. V.; Swamy, P. M. (Indian Forester, 1995)
Seasonal changes in the growth rates of seven tree saplings were studied for a period of one year. Maximum leaf area, number of branches, stem girth, shoot and root length were observed in the winter season in all the seven tree species. The growth rates showed month to month and species to species variations.